Secondary Metabolites and Antioxidant Activity of Purwoceng (Pimpinella Pruatjan) Root Extracts from Various Hydroponic Planting Techniques - Irmanida Batubara; Shadila Fira Asoka; Eni Sumarni; Herry Suhardiyanto; Mohamad Solahudin; Slamet Widodo; Supriyanto Supriyanto; Eti Rohaeti; Yudiwanti Wahyu; Folkes Laumal; Erniati Erniati (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Purwoceng (Pimpinella pruatjan) is Indonesia’s native herbs that grow in the highlands but its existence is hard to find. The reason is that purwoceng is difficult to cultivate. A controlled factor in cultivation, such as hydroponic types and nutrient concentration, can be used as a solution to this problem. Hydroponic types and nutrient concentration treatments can affect the secondary metabolites and antioxidant activity of the purwoceng root extract produced. This study aimed to determine total phenolic and flavonoid content, as well as antioxidant activity in three different hydroponic systems (nonrecirculating drip, recirculating drip, and nutrient film technique (NFT)) and two nutrient concentrations (1.5‰ and 2.0‰). The combination of recirculating drip with low nutrient concentration was the best treatment to produce an extract with high phenolic and flavonoid content. Purwoceng root extracts from nonrecirculating with high nutrient concentrations produced high antioxidant activity. The characteristics of extracts from recirculating with low nutrient concentrations were similar to those from the nonrecirculating drip. In contrast, extracts from recirculating with high nutrient concentrations were closer to extracts from NFT, proven by principal component and heat map analysis. Antioxidant activity related to total phenolic content, also the presence of betaine and bergapten in purwoceng root extracts. Keywords: Flavonoid content, NFT, Nonrecirculating drip, Phenolic content, Recirculating drip